2017
DOI: 10.1155/2017/6063850
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Moringa oleifera on HBV Genotypes C and H Transiently Transfected Huh7 Cells

Abstract: Chronic hepatitis B infection treatment implicates a long-lasting treatment. M. oleifera extracts contain compounds with antiviral, antioxidant, and antifibrotic properties. In this study, the effect of M. oleifera was evaluated in Huh7 cells expressing either HBV genotypes C or H for the antiviral, antifibrotic, anti-inflammatory, and antioxidative responses. Huh7 cells were treated with an aqueous extract of M. oleifera (leaves) at doses of 0, 30, 45, or 60 μg/mL. The replicative virus and TGF-β1, CTGF, CAT,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 46 publications
(44 reference statements)
0
23
0
2
Order By: Relevance
“…A novel arabinogalactan, Moringa oleifera polysaccharide 1 (MOP-1), has been isolated from the leaves of MO showing strong antioxidant properties [20]. In addition, it has also been reported that MO leaves may be of use in viral [21] and bacterial infections [22]. In general, MO leaves have been reported to be of possible benefit for several chronic diseases including cardiovascular conditions, liver diseases, cancer, insulin resistance, and diabetes.…”
Section: Leavesmentioning
confidence: 99%
“…A novel arabinogalactan, Moringa oleifera polysaccharide 1 (MOP-1), has been isolated from the leaves of MO showing strong antioxidant properties [20]. In addition, it has also been reported that MO leaves may be of use in viral [21] and bacterial infections [22]. In general, MO leaves have been reported to be of possible benefit for several chronic diseases including cardiovascular conditions, liver diseases, cancer, insulin resistance, and diabetes.…”
Section: Leavesmentioning
confidence: 99%
“…It facilitates phytate breakdown by action of phytase enzymes which lead to absorption of phosphorus [13]. Moringa oleifera plants treats Hepatitis B infection in humans [14].…”
Section: Introductionmentioning
confidence: 99%
“…From this point of view, to evaluate antiretroviral activity of different extracts of M. oleifera, Nworu and collaborators [321], used a specific antiviral screening technique, demonstrating that three different extracts of M. oleifera were able to inhibit infectious power of HIV-1 lentiviral particles. In a recent research, [322] the antiviral activity of aqueous extracts of M. oleifera leaves was evaluated on Huh7 cell line. In particular, these extracts were able to modulate the pgRNA levels and HBsAg secretion positively in Huh7 cells transfected with genotypes C and H of HBV.…”
Section: Moringamentioning
confidence: 99%